Consensus Nomenclature for in vivo Imaging of Reversibly Binding Radioligands - Innis, Robert B; Cunningham, Vincent J; Delforge, Jacques; Fujita, Masahiro; Gjedde, Albert; Gunn, Roger N; Holden, James; Houle, Sylvain; Huang, Sung-Cheng; Ichise, Masanori; Iida, Hidehiro; Ito, Hiroshi; et al. (Journal of cerebral blood flow and metabolism, 2007)
An international group of experts in pharmacokinetic modeling recommends a consensus nomenclature to describe in vivo molecular imaging of reversibly binding radioligands.An international group of experts in pharmacokinetic modeling recommends a consensus nomenclature to describe in vivo molecular imaging of reversibly binding radioligands.